The role of technology in high-performance sport - Hahn, A. (5. Asia-Pacific Congress on Sport Technology 2011 Melbourne, 2011)
Technological developments are influencing almost every aspect of modern high performance sport Over the past 30 years, they have totally transformed training and competition environments The high performance sector is very accepting of technologies that assist pursuit of its core functions There remains great scope for future technological innovation